Elucidation of Effectiveness of Dye Absorption as a Probe to Determine The Chemical Reactivity of Cellulose Nanofibrils - Salem, Khandoker Samaher; Kasera, Nitesh Kumar; Pal, Lokendra; Jameel, Hasan; Lucia, Lucian A (Dhaka University Journal of Applied Science and Engineering, 2023)
Cellulose nanofibrils (CNF) has earned substantial attention as a sustainable biopolymer due to environmental consciousness and the implementation of strict regulations for the remediation of single use plastics. However, the existing processing strategies rely on intensive mechanical grinding and quality of production is often measured by physical changes such as fines which completely overlooks chemical changes such as exposure of large numbers of hydroxyls which significantly compromises desirable properties. Therefore, we use dye absorption technique to measure the chemical reactivity of the CNF. The CNF was produced from bleached hardwood kraft pulp (BHK) with different extent of fibrillation by varying the cumulative mechanical energy and then acetylation and dye absorption were used as a tool to investigate its chemical reactivity. The degree of substitution (DS) of the CNF reached a highest value and subsequently, it decreased to lesser values though the CNF were produced using higher cumulative energies. The dye absorption by CNF samples also followed the similar trend like the DS value of the CNF samples. The dye absorption was affected by the hydration shell formed by the hard-to-remove (HR) water molecules and the self-aggregation of cellulose hydroxyls at higher fibrillation, which hindered accessibility of the dye molecules to absorption cites. Therefore, this technique could be used as a new useful probing tool to determine the nanocellulose reactivity and might be a potential physicochemical strategy to produce and chemically modify CNF in an efficient and sustainable way to optimize its performance for different applications. DUJASE Vol. 7 (2) 39-46, 2022 (July)